Legal Protection Towards Workers Under Collective Labor Agreement - Grace Albertin A. (NOTARIIL Jurnal Kenotariatan, 2018)
The Collective Labor Agreement is one of working agreements negotiated by workers joining the trade union organizations together with employers as employment providers. In the making of the agreement, it must first be negotiated by both parties. In particular, in order for the trade union to attend the negotiation, it must meet the requirement stipulated in the provisions of law and regulation stipulated in Laws Number 13 Year 2003 on Labor and Ministerial Regulation Number 28 Year 2014. The two regulations have non-interrelated arrangements or in other words it can be said as conflict of norms, hence this present study is conducted to examine the validity of enactment of collective labor agreement in a company and the legal protection for the trade union under the collective labor agreement. The study makes use of normative research method, i.e. by reviewing the documents of legislations and the literatures with legislation and conceptual approach. The result of the study shows that the validity of enactment of collective labor agreement refers to its relation with legal validity of a norm in the principle of legislation lex superior derogate lex impriori, so that the labor laws is enacted, but not apart from the role of labor ministerial regulations. The validity of the legitimate terms of an agreement is also needed to underlie a collective agreement. The legal protection that can be applied for trade union is in the form of supervision as well as legal protection both preventive and repressive outlined in the collective labor agreement content.